Serial monogamy and double brooding in the White-cheeked (Bahama) Pintail Anas bahamensis - Sorenson, Lisa Guminski; Woodworth, Bethany L; Ruttan, Lore M; McKinney, Frank (Wildfowl, 1992)
We describe the occurrence of two new phenomena in the behavioral ecology of the White-cheeked Pintail. In 1989, a probable case of serial monogamy was documented: Behavioral observations of marked individuals and DNA fingerprinting showed that a male paired with two females in succession and successfully fathered two broods in one season. In 1990, double brooding was recorded: a marked female successfully fledged one brood and then laid a second clutch approximately one month later. Although occurring rarely, these phenomena provide further evidence of the increased variability in the reproductive tactics of individuals in species with variable and extended breeding seasons.